2023
DOI: 10.3390/brainsci13060900
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Soft Robotic Gloves in Stroke Patients: A Systematic Review and Meta-Analysis of Randomized Controlled Trials

Abstract: Wearable robotic devices have been strongly put into use in both the clinical and research fields of stroke rehabilitation over the past decades. This study aimed to explore the effectiveness of soft robotic gloves (SRGs) towards improving the motor recovery and functional abilities in patients with post-stroke hemiparesis. Five major bibliographic databases, PubMed, Embase, Cochrane Library, Web of Science, and the Physiotherapy Evidence Database, were all reviewed for enrollment regarding comparative trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
1
0
Order By: Relevance
“…When considering the application of robotic hand devices as a training tool during supervised therapy sessions, multiple reviews, all focusing on stroke rehabilitation, have concluded that robot-assisted hand training has a superior effect on improvement of motor function, dexterity and spasticity [ 36 38 ] compared to conventional therapy. Those improvements persisted at one to 12 weeks follow-up [ 38 ]. Although those reviews included studies with non-robotic devices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…When considering the application of robotic hand devices as a training tool during supervised therapy sessions, multiple reviews, all focusing on stroke rehabilitation, have concluded that robot-assisted hand training has a superior effect on improvement of motor function, dexterity and spasticity [ 36 38 ] compared to conventional therapy. Those improvements persisted at one to 12 weeks follow-up [ 38 ]. Although those reviews included studies with non-robotic devices (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The non-modifiable risk factors of each include age, sex, race, and genetics. The risk increases as you get older; the risk is higher in men at a younger age, but the risk of death is higher overall in women [6]. The effect of physiotherapy rehabilitation in MCA stroke is a crucial aspect of patient care, aiming to address the diverse physical and functional challenges that arise from this type of stroke [7].…”
Section: Introductionmentioning
confidence: 99%
“…Robotic-assisted hand rehabilitation is often used to improve motor function in strokerelated paralyzed hands and has shown significant therapeutic benefits compared with conventional treatment [10,11]. Wearable robots have gained attention as they can embody motor functions tailored to various hand movements by collecting motion data or physiological signal data on the user's hand movements through device-mounted sensors [12]. These robots also reportedly have a positive effect on hand motor function recovery in patients with stroke [13].…”
Section: Introductionmentioning
confidence: 99%